TIMELINE FOR THE DOUBLE ANTIPLATELET THERAPY. FACTS AND SUGGESTIONS - O. L. Barbarash; V. V. Kashtalap (Российский кардиологический журнал)
The review article provides with recent data on the crucial cardiology problems — duration of double antiplatelet therapy (DAPT) in patients with different types of ischemic heart disease. The analysis is provided of actual clinical guidelines on this issue, the results of recent clinical trials are highlighted, as of metaanalyses. Based on the results of international trials, the necessity postulated of thorough assessment of risk and safety for either prolongation or shortening of DAPT, and some possible indications provided for these changes in 12-month DAPT.